Model Pembelajaran Project Based Learning untuk Meningkatkan Ketuntasan Hasil Belajar Numerasi Siswa Kelas 1 SDN 2 Ngrawan - Irdani, Laili Rahma; Santia, Ika (LP. Ma'arif Janggan Magetan, 2023)
This research was motivated by the low level of complete learning outcomes for grade 1 students at SD Negeri 2 Ngrawan regarding numeracy. The aim of this research is to improve the completeness of student learning outcomes. This type of research is classroom action research. Classroom action research was carried out in two cycles. The subjects of this research were class 1 students consisting of 12 students. Techniques for collecting data are tests, observation and documentation. The results of the research show that carrying out learning activities by applying the project based learning model can improve the completeness of students' numeracy learning outcomes. This is indicated by an increase in test results from each cycle. In cycle I, the percentage of student success reached 25%. Meanwhile, in cycle II, the percentage of student success reached 83%. The research can be said to be successful because the percentage of success reaches ≥80%. The conclusion of this research is that the project based learning model can improve the completeness of students' numeracy learning outcomes.